Studying the Interacting Partners of RNA Polymerase III transcription factors, TFIIIB and TFIIIC - Nanda, Ishita (My University, 2014)
Eukaryotes use three types of RNA polymerases for the transcription of their large gene repertoire. Each type of eukaryotic RNA polymerase is dedicated to the synthesis of a particular class of RNA species: RNA polymerase I synthesizes ribosomal RNAs; RNA polymerase II synthesizes messenger RNA molecules which later get translated into protein molecules; RNA polymerase III synthesizes transfer RNA and a few non-coding RNA molecules. Out of the three, RNA Polymerase III is the least studied in the model organism used which is S.Cerevisiae. RNA Pol III has two basic transcription factors, TFIIIB and TFIIIC, each having 3 and 6 subunits respectively. The thesis focuses on RNA Pol III interactome in S. cerevisiae. The work highlights the interacting partners of Transcription Factors IIIC and IIIB by checking their interaction with their subunits, TFC1 and BRF1 respectively. The target proteins SPT16,SWC5, PAF1, MAF1. TAF14 and TAF12 that have been selected, are known to play a role with RNA Pol II transcription also.
MT, DBTS
Keywords: RNA pol III, TFIIIB, TFIIIC, BRF1, TFC1, immuno-precipitation